2018
DOI: 10.1212/wnl.0000000000006617
|View full text |Cite
|
Sign up to set email alerts
|

Concussion BASICS III

Abstract: ObjectiveTo evaluate changes in serum biomarker concentrations (β-amyloid peptide 42 [Aβ42], total tau, ubiquitin carboxy-terminal hydrolyzing enzyme L1, S100 calcium binding protein B [S100B], glial fibrillary acidic protein [GFAP], microtubule associated protein 2 [MAP2], and 2′,3′-cyclic-nucleotide 3′-phosphodiesterase [CNPase]) after sport-related concussion (SRC) in a sample of collegiate athletes. Associations with clinical outcomes were also investigated.MethodsParticipants in this case-control study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…There were no differences among the different groups of athletes in the serum levels of astroglial damage markers (GFAP, BLBP, PEA15), neuronal and axonal injury makers (UCH-L1, NfL, tau and p-tau) or HMGB1 (a marker of cellular damage and initiator of inflammatory response). These findings are congruent with previous findings reporting no association between a HoC and fluid biomarkers outside the acute (i.e., < 14 days) postinjury phase (32)(33)(34). For example, in a study of 415 athletes, there were no significant relationships between the number of previous concussions or cumulative head injury with baseline levels of serum biomarkers GFAP, S100B, and UCH-L1 (32).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…There were no differences among the different groups of athletes in the serum levels of astroglial damage markers (GFAP, BLBP, PEA15), neuronal and axonal injury makers (UCH-L1, NfL, tau and p-tau) or HMGB1 (a marker of cellular damage and initiator of inflammatory response). These findings are congruent with previous findings reporting no association between a HoC and fluid biomarkers outside the acute (i.e., < 14 days) postinjury phase (32)(33)(34). For example, in a study of 415 athletes, there were no significant relationships between the number of previous concussions or cumulative head injury with baseline levels of serum biomarkers GFAP, S100B, and UCH-L1 (32).…”
Section: Discussionsupporting
confidence: 89%
“…However, other studies have failed to find a relationship between RHI exposure and neurological outcomes in American footballers (33), suggesting other factors may have contributed to our findings. For example, there are a number of preclinical studies (34), and initial human studies (6,35,36) indicating that males and females have inherent biological differences in their response to mTBI. A possible contributor to differences in circulating biomarkers between males and females are sex hormones, as well as fluctuation in hormones across the female menstrual cycle (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…For example, higher GFAP levels acutely following an mTBI are associated with having lesions detected by both computed tomography and magnetic resonance imaging 20 and by identifying athletes with an SRC compared with controls with no injuries. 21 Indeed, our group has previously reported that higher GFAP concentrations were associated with SRCs with LOC. 22 Therefore, these results may actually support the association, given that the group with less than 14 days before RTS did report significantly higher incidence of LOC (Table 1).…”
Section: Jama Network Open | Physical Medicine and Rehabilitationmentioning
confidence: 91%
“…Several candidate biomarkers have emerged as potential blood tests to aid concussion management. Aside from objectively assessing SRC presence, such markers have been suggested to predict and monitor recovery, while advancing our understanding of the underlying pathophysiological mechanisms of concussion (4)(5)(6)(7). Nonetheless, there has been a preponderant focus on male athletes, and very few studies have explored sex-related variability of brain injury biomarkers and their relationships with the underlying neuropathological and clinical characteristics of SRC (8,9).…”
Section: Introductionmentioning
confidence: 99%